2011
DOI: 10.1017/s0033291711000067
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effects of subjective memory impairment and ApoE4 genotype on episodic memory and hippocampal volume

Abstract: The negative effect of ApoE4 on episodic memory and hippocampal volume in SMI supports SMI as a prodromal condition of AD. The positive effects of ApoE4 in subjects without SMI adds to a number of reports on positive ApoE4 effects in young and very old individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 47 publications
7
41
0
Order By: Relevance
“…We found an increase in amyloid deposition and abnormal levels of CSF amyloid and tau in older adults with SMC, which was strongly associated with APOE ε4 carrier status. However, we did not observe differences in glucose metabolism and MTL atrophy in this population, even in SMC APOE ε4+, as has been previously reported [4, 13, 17, 19, 21, 23, 28, 46, 47]. Given the previous research in participants with SCD/SMC, the lack of hypometabolism or atrophy is somewhat surprising.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We found an increase in amyloid deposition and abnormal levels of CSF amyloid and tau in older adults with SMC, which was strongly associated with APOE ε4 carrier status. However, we did not observe differences in glucose metabolism and MTL atrophy in this population, even in SMC APOE ε4+, as has been previously reported [4, 13, 17, 19, 21, 23, 28, 46, 47]. Given the previous research in participants with SCD/SMC, the lack of hypometabolism or atrophy is somewhat surprising.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown that older adults with SCD/SMC have an increased risk for future progression to AD [516], as well as AD-like changes in neuroimaging and cerebrospinal fluid (CSF) biomarkers [4, 13, 1727]. In addition, SCD/SMC participants who are carriers of the most commonly reported genetic variant associated with late onset AD, the apolipoprotein E ( APOE) ε4 allele, show greater medial temporal lobe (MTL) hypometabolism and atrophy, increased cerebral amyloid, as well as altered CSF measures of amyloid and tau [22, 23, 28, 29]. However, to date, no studies have looked at the role of APOE ε4 status in SCD/SMC across a comprehensive multimodal panel of the major imaging and CSF AD biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…In a small cross-sectional study, APOE ε4 carriers with SCC referred to a memory clinic had lower hippocampal volumes than those without memory impairment [39]. APOE ε4 carriers with SCC (defined by a single question, ie, reporting occasional forgetting names or forgetting where one placed objects) had greater brain hypometabolism (a marker of loss of synaptic function due to neuronal damage) in the same regions as those affected in AD patients, and increased levels of AD biomarkers in the cerebrospinal fluid, as compared to carriers without subjective memory concerns [40].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence from some memory clinic and population-based studies of an overrepresentation of the APOE ε4 allele in SCD, a particular association of APOE ε4 and biomarker evidence for AD in SCD, and an effect of APOE ε4 on the prospective risk of cognitive decline in SCD [5861]. To further elucidate the potential use of the APOE genotype in predicting preclinical AD and cognitive decline in SCD, it should be reported in SCD studies, if available.…”
Section: Apolipoprotein E Genotypementioning
confidence: 99%